Analyzing the Effect of Product Completeness in marketing - sari dewi, lati (LP2M Universitas Perjuangan Tasikmalaya, 2024)
This study aims to find out an empirical of: 1) Completeness of products at Mega Baja Iron Shop Tasikmalaya. 2) Purchasing decisions at Mega Baja Iron Shop Tasikmalaya. 3) The Effect of Product Completeness on Purchasing Decisions at Mega Baja Iron Shop Tasikmalaya.The research method used in this study is a descriptive method with a quantitative approach. Responden in the study was 96 people. The results of this study show that: 1) The interpretation of product completeness at Mega Baja Iron Shop Tasikmalaya is considered good. 2) The interpretation of the interpretation of the purchasing decision at Mega Baja Iron Shop Tasikmalaya considered very good. 3) Product completeness affects purchasing decisions at Mega Baja Iron Shop Tasikmalaya